Domestic Macroeconomic Shocks and International Disturbances on the Malaysian Stock Market - Yeap, Hong Chen (2008)
This paper examines the impacts of the domestic macroeconomic shocks and international disturbances on the Malaysian stock market. The priority objective of this paper is to determine the existence, but not the strength of the causal relationship among the variables. Henceforth, domestic macroeconomic shocks and international disturbances are determined separately using two models. The long-run relationship is determined using Johansen-Juselius multivariate cointegration analysis. The short-run dynamic fluctuations are captured using Granger causality test under Vector Error-correction model (VECM) framework. The results suggest that real output plays an important role in generating macroeconomic fluctuations, while international disturbances originated from the US market are the most influential. From a policy point of view, policy designs should be focused on real output growth and alignment of policies with those of the US in alleviating domestic fluctuations.